EGU European Geosciences Union / Buoyant calving and ice-contact lake evolution at Pasterze Glacier (Austria) in the period 1998-2019 - Kellerer-Pirklbauer, Andreas; Avian, Michael; Benn, Douglas I.; Bernsteiner, Felix; Krisch, Philipp; Ziesler, Christian (Universitätsbibliothek, 2020)
Abstract: Rapid growth of proglacial lakes in the current warming climate can pose significant 24 outburst flood hazards, increase rates of ice mass loss, and alter the dynamic state of glaciers. 25 We studied the nature and rate of proglacial lake evolution at Pasterze Glacier (Austria) in the 26 period 1998-2019 using different remote sensing (photogrammetry, laserscanning) and 27 fieldwork-based (GPS, time-lapse photography, geoelectrical resistivity tomography/ERT, and 28 bathymetry) data. Glacier thinning below the spillway level and glacier recession caused 29 flooding of the glacier, initially forming a glacier-lateral to supraglacial lake with subaerial and 30 subaquatic debris-covered dead-ice bodies. The observed lake size increase in 1998-2019 31 followed an exponential curve (1998: 1900 m²; 2019: 304,000 m²). ERT data from 2015 to 2019 32 revealed widespread existence of massive dead-ice bodies exceeding 25 m in thickness near the 33 lake shore. Several large-scale and rapidly occurring buoyant calving events were detected in 34 the 48 m deep basin by time-lapse photography, indicating that buoyant calving is a crucial 35 process for fast lake expansion. We identified a sequence of processes: glacier recession into a 36 basin and glacier thinning below spillway-level; glacio-fluvial sedimentation in the glacial 37 proglacial transition zone covering dead ice; initial formation and accelerating enlargement of a 38 glacier-lateral to supraglacial lake by ablation of glacier ice and debris-covered dead ice forming 39 thermokarst features; increase in hydrostatic disequilibrium leading to destabilization of ice at 40 the lake bottom or at the near-shore causing fracturing, tilting, disintegration or emergence of 41 new icebergs due to buoyant calving; and gradual melting of icebergs along with iceberg 42 capsizing events. We conclude that buoyant calving, previously not reported from the European 43 Alps, might play an important role at alpine glaciers in the future as many glaciers are expected 44 to ...